Antidrug antibodies to adalimumab do not associate with immunologically related adverse events - Tourdot, Sophie; Vazquez-Abad, Maria-Dolores; Cox, Donna S.; Cai, Chun-Hua; Wang, Karen; Zhang, Wuyan; Lepsy, Christopher (Frontiers in Immunology, 2025)
IntroductionUnwanted immune responses (UIRs) to biologics can negatively impact treatment efficacy and pharmacokinetics and/or induce adverse events (AEs). We characterized the UIR profile of adalimumab (ADL) using data from a phase 3, randomized, interchangeability study of reference ADL (ADL-REF; Humira®) and ADL biosimilar PF-06410293 in patients with rheumatoid arthritis (RA).MethodsEligible patients (18−70 years, moderate-to-severe active RA) received ADL-REF from weeks 0−10 (lead-in period) then were randomized 1:1 to: 3 switches between PF-06410293 and ADL-REF or continuous ADL-REF treatment until week 32. As interchangeability of PF-06410293 with ADL-REF was previously demonstrated, data were combined across groups to describe the development of antidrug antibodies (ADAs) and their impact on pharmacokinetics and immunologically related AEs. Pharmacokinetic endpoints included maximum observed serum concentration (Cmax), area under serum concentration–time curve over dosing interval (AUCtau), time of maximum observed serum concentration (Tmax), average serum concentration (Cav), and apparent clearance (CL/F), determined from robust pharmacokinetic sampling during weeks 30–32; and predose concentrations (Ctrough) at prespecified sampling time points. Other endpoints: patients (%) with ADA-positive and neutralizing ADA (NAb)-positive samples, time of first ADA/NAb detected, ADA titers over time, persistence of ADA/NAb, and immunologically related AEs by ADA/NAb status.ResultsOf 427 randomized patients, 59% were ADA-positive, 52% had persistent ADA, 14% were NAb-positive, and 10% had persistent NAb. In most patients, ADA/NAb first developed within 16 weeks of ADL treatment regardless of pre-existing (baseline day 1) ADA. ADA/NAb titers stabilized by week 16 without boosters. Ctrough was lower in patients with ADA-positive than ADA-negative samples throughout the study. From weeks 30–32, AUCtau, Cmax, and Cav were lower in ADA-positive than ADA-negative samples at week 30, especially in patients with ADA-positive/NAb-positive samples. Only 3% of patients had immunologically related AEs. Most were injection site and hypersensitivity reactions, and none were considered severe or serious or associated with the presence of ADA/NAb. Presence of pre-existing ADA did not increase the potential for immunologically related responses to ADL.ConclusionsPresence of ADA (with or without NAb) was associated with lower drug concentrations and faster clearance but not with the development of immunologically related AEs.Clinical trial registrationClinicalTrials.gov, identifier NCT0423021.